Nutritional status and quality of life in older adults: systematic review - Angulo, Ashley A.; Rodríguez, Daliannis; García, Mario A. (Revista Gregoriana de Ciencias de la Salud, 2024)
This study analyzed nutritional status and its impact on the quality of life of older adults in different socioeconomic contexts. The objective was to identify the factors associated with malnutrition in this population and its relationship with the appearance of comorbidities. A systematic review of the literature was carried out, selecting 30 articles published in the last five years. The results showed a high prevalence of malnutrition, especially in rural areas, and its association with chronic diseases such as osteoarthritis and diabetes. Additionally, improvements in quality of life were observed when nutritional interventions and physical activity programs were implemented. The conclusions highlight the need to strengthen public health policies focused on the prevention of malnutrition and the development of sustainable interventions for older adults in vulnerable situations.